Community Service on Strengthening Health Promotion Policy Implementation to Improve Hospital Services in Tuban - Sugiyono Sugiyono (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
This community service aimed to strengthen the implementation of health promotion policies in order to improve hospital services in Tuban Regency. The program was designed to address existing gaps in health promotion practice, particularly limited human resources, suboptimal use of educational media, and low integration of health promotion into routine hospital services. The scope of activities included needs assessment, training, mentoring, and evaluation involving healthcare workers and hospital management. The methods used consisted of participatory approaches through focus group discussions, interactive training sessions, development of audiovisual health education materials, and direct mentoring in implementing health promotion activities. The results showed a significant increase in healthcare workers’ knowledge and skills, as reflected by improved pre-test and post-test scores. The results showed that staff knowledge increased by 24.3% (from an average pre-test score of 60.5% to 84.8%), while patient satisfaction improved from 71% to 88% after the implementation of digital media such as short videos and digital leaflets in waiting areas. This community service demonstrated that strengthening health promotion policy implementation—through participatory learning and digital innovation—can enhance hospital service quality, increase patient satisfaction, and support better health outcomes in Tuban Regency.